Granular Characteristics and Infrared Extinction Coefficients of Graphite Aerosol. (2015) - Xuanyu, Wang; Wenjie, Dong; Minhui, Pang; haitao, Bai; Rui, Hu
Abstract: In order to study the extinction performance of graphite aerosol, some preprocessed graphite particles is analyzed by a microscope to determine theirs circularity index, maximum and minimum diameter, average diameter, aspect ratio. The sedimentation rate of graphite particles is calculated against atmospheric environment. The mass extinction coefficients of graphite aerosol to 3-5 μm and 8-14 μm infrared emission have been quantitatively tested by a Fourier transform infrared spectrometer in a micro aerosol-chamber with a volume 4000 ml and an optical length 0.22m. By the analysis, the minimum diameter of the graphite particles is 0.76 μm and the maximum diameter is 12.76 μm, the average diameter is 5.64 μm, the average circularity index is 0.96, the average aspect ratio is 1.4, the sedimentation rate is 0.00212m/s, which indicates the graphite particles have a good diffusing and suspending performance to form a steady aerosol system in atmospheric environment. By the experimental result, the mass extinction coefficient of the graphite aerosol to 3-5 μm infrared emission is 0.86m 2 /g while to 8-14 μm is 0.75m 2 /g, which indicates the graphite aerosol has a good performance to attenuate infrared emission both in 3-5 μm and in 8-14 μm band waves.